Journal Economics, business & accountancy: THEORETICAL TESTING ON SERVICE QUALITY AND PRODUCT INNOVATION OF SMALL-MICRO CREDIT BANKS (A CASE STUDY) - Mohamad Dimyati (PPPM Perbanas, 2011)
The research topic is a theoretic influence of service quality and product innovation on customerloyalty which are mediated by customer satisfaction and customer trust borrowing microand small scale credit of public bank in Jember Regency. The research examines the influencesof: service quality on customer satisfaction and customer trust as well as customerloyalty, customer satisfaction on customer loyalty, product innovation on customer trust andcustomer loyalty, customer trust on customer loyalty borrowing micro and small scale creditof public bank in Jember Regency